PENGAMATAN SYAFAQ DI KARIMUN JAWA MENGGUNAKAN ANALISA PERBANDINGAN INTENSITAS CAHAYA DAN 3D SURFACE - Hawwin Chilyatina; Ahmad Adib Rofiuddin; M. Nur Iskandar Fajri (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The criteria for shafaq remain a matter of debate among Muslims, particularly among scholars who propose varying solar depression angles, such as -15°, -18°, -19°, -19.5°, and -20°. These differences directly affect the determination of prayer times, as the start of prayer depends on the chosen solar elevation angle. This issue is of particular concern to the Muslim community, especially in relation to the onset of the Isha prayer. In this study, the author conducts observations to examine the shafaq phenomenon. Data were collected through observations on Karimun Jawa Island using a smartphone camera (Poco F1) with ISO 1600, an 8-second shutter speed, and 15-second intervals between photos. This research employs a qualitative method with a descriptive-comparative approach by comparing two or more variables, utilizing two types of analysis: light intensity comparison and 3D Surface analysis, both using features available in the Astro ImageJ application. The study demonstrates that the shafaq phenomenon can be effectively analyzed using both methods, although differences were observed. The light intensity comparison method detected the shafaq approximately 10 minutes later than the 3D Surface analysis.